France : Financial Sector Assessment Program-Technical Note-Risk Analysis of Banking and Insurance Sector. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2019)
This technical note presents risk analysis of banking and insurance sector in France. The assessment is based on stress tests, which simulate the health of banks, insurers under severe yet plausible (counterfactual) adverse scenarios. The stress tests reveal that banks and insurers would be resilient against simulated shocks, although some challenges remain. French banks have improved their capitalization and asset quality; however, profitability remains challenged. The report also highlights that profitability is pressured on both the income and expense sides. Banks' ability to generate higher interest income is constrained by persistently low interest rates, and market businesses including trading activities have contracted in recent years. Growth-at-risk (GaR) analysis shows that the biggest contributing factors to the risk of growth are cost of funding and stock market prices. Financial conditions continue to tighten gradually since mid-2017; though the overall conditions remain accommodative. Risks stemming from loans to households seem to be contained over the short- to medium-term horizon, given relatively strong households' balance sheets, no evidence of significant misalignment in house prices, social safety nets, and fixed interest rates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet